Acetolactate synthases MoIlv2 and MoIlv6 are required for infection‐related morphogenesis in Magnaporthe oryzae. (19th June 2013) - Du, Yan; Zhang, Haifeng; Hong, Li; Wang, Jiamei; Zheng, Xiaobo; Zhang, Zhengguang
Summary: Amino acids are important components in the metabolism of a variety of pathogens, plants and animals. Acetolactate synthase (ALS) catalyses the first common step in leucine, isoleucine and valine biosynthesis, and is the target of several classes of inhibitors. Here, MoIlv2, an orthologue of the Saccharomyces cerevisiae ALS catalytic subunit Ilv2, and MoIlv6, an orthologue of the S. cerevisiae ALS regulatory subunit Ilv6, were identified. To characterize MoILV2 and MoILV6 functions, we generated the deletion mutants Δ Moilv2 and Δ Moilv6. Phenotypic analysis showed that both mutants were auxotrophic for leucine, isoleucine and valine, and were defective in conidial morphogenesis, appressorial penetration and pathogenicity. Further studies suggested that MoIlv2 and MoIlv6 play a critical role in maintaining the balance of intracellular amino acid levels. MoIlv2 and MoIlv6 are both localized to the mitochondria and the signal peptide of MoIlv6 is critical for its localization. In summary, our evidence indicates that MoIlv2 plays a crucial role in isoleucine and valine biosynthesis, whereas MoIlv6 contributes to isoleucine and leucine biosynthesis; both genes are required for fungal pathogenicity. This study indicates the potential of targeting branched‐chain amino acid biosynthesis for anti‐rice blast management.